Measuring Customer loyalty on New Consumer Products through Customer Satisfaction in Jakarta Indonesia - Renwarin, Joseph M J (Advances in Social Sciences Research Journal, 2018)
The quality of a product has an important role in creating customer loyalty and customer satisfaction. The purpose of this study is to determine the effect of product quality on customer loyalty with customer satisfaction as a mediating variable through a survey on Advan consumers in Jakarta. This research is a quantitative research using causal method. The population in this study is the buyers of Advan smartphone, with the sample as many as 250 chosen by the sampling technique using Lemeshow formula. Data is collected by means of questionnaires. The results indicate that product quality significantly influences customer loyalty; product quality also has a significant effect on customer satisfaction; and customer satisfaction significantly influences loyalty, or in the other words, customer satisfaction can mediate the influence of product quality on customer loyalty.